Composite properties of high-strength polyethylene fiber-reinforced cement and cementless composites. (15th March 2016) - Choi, Jeong-Il; Song, Keum-Il; Song, Jin-Kyu; Lee, Bang Yeon
Abstract: This paper presents an experimental study of the composite properties of cement based- and alkali-activated ground-granulated blast furnace slag (GGBS) based composites reinforced by high-strength polyethylene fibers and a discussion of the different behaviors of the two types of binder-based composites. A series of experiments, including those to test the density, compression, and uniaxial tension, was performed to characterize the mechanical properties of the composite. The test results indicated that an alkali-activated GGBS composite shows a higher tensile strain capacity with smaller crack widths and crack spacings than a cement-based composite, although the alkali-activated GGBS composite showed lower compressive and lower tensile strength than the cement-based composite with the same water-to-binder ratio. It was also observed that the alkali-activated GGBS-based composite has higher ratio of the tensile strength to the compressive strength than the cement-based composite.